Scaling Up Maternal Mental healthcare by Increasing access to Treatment (SUMMIT) through non-specialist providers and telemedicine: a study protocol for a non-inferiority randomized controlled trial - Singla, D; Meltzer-Brody, S; Silver, RK; Vigod, SN; Kim, JJ; Clark, D; Dennis, CL; Patel, V (BioMed Central, 2021)
Background Depression and anxiety impact up to 1 in 5 pregnant and postpartum women worldwide. Yet, as few as 20% of these women are treated with frontline interventions such as evidence-based psychological treatments. Major barriers to uptake are the limited number of specialized mental health treatment providers in most settings, and problems with accessing in-person care, such as childcare or transportation. Task sharing of treatment to non-specialist providers with delivery on telemedicine platforms could address such barriers. However, the equivalence of these strategies to specialist and in-person models remains unproven. Methods This study protocol outlines the Scaling Up Maternal Mental healthcare by Increasing access to Treatment (SUMMIT) randomized trial. SUMMIT is a pragmatic, non-inferiority test of the comparable effectiveness of two types of providers (specialist vs. non-specialist) and delivery modes (telemedicine vs. in-person) of a brief, behavioral activation (BA) treatment for perinatal depressive and anxiety symptoms. Specialists (psychologists, psychiatrists, and social workers with ≥ 5 years of therapy experience) and non-specialists (nurses and midwives with no formal training in mental health care) were trained in the BA protocol, with the latter supervised by a BA expert during treatment delivery. Consenting pregnant and postpartum women with Edinburgh Postnatal Depression Scale (EPDS) score of ≥ 10 (N = 1368) will be randomized to one of four arms (telemedicine specialist, telemedicine non-specialist, in-person specialist, in-person non-specialist), stratified by pregnancy status (antenatal/postnatal) and study site. The primary outcome is participant-reported depressive symptoms (EPDS) at 3 months post-randomization. Secondary outcomes are maternal symptoms of anxiety and trauma symptoms, perceived social support, activation levels and quality of life at 3-, 6-, and 12-month post-randomization, and depressive symptoms at 6- and 12-month post-randomization. Primary analyses are per-protocol and intent-to-treat. The study has successfully continued despite the COVID-19 pandemic, with needed adaptations, including temporary suspension of the in-person arms and ongoing randomization to telemedicine arms. Discussion The SUMMIT trial is expected to generate evidence on the non-inferiority of BA delivered by a non-specialist provider compared to specialist and telemedicine compared to in-person. If confirmed, results could pave the way to a dramatic increase in access to treatment for perinatal depression and anxiety. Trial registration ClinicalTrials.gov NCT 04153864. Registered on November 6, 2019.